Photocatalysis Fundamentals, Materials and Applications - Zhang, Jinlong; Tian, Baozhu; Wang, Lingzhi; Xing, Mingyang; Lei, Juying; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book describes the photocatalytic mechanism, factors affecting photocatalytic activity, design and preparation of different kinds of nanostructured photocatalysts, and their applications in the environmental and energy fields. Further, it illustrates a broad range of modification methods including ion-doping, heterojunction, noble metal deposition, morphological control and sensitizations, which are used to extend the light absorption range of photocatalysts and reduce recombination between electrons and holes. Promising applications include water splitting, contaminant decomposition and photocatalytic reduction of CO2, which are closely related to environmental redemption and new energy development. The book offers an intriguing and useful guide for a broad readership in various fields of catalysis, material sciences, environment and energy.
Part I Photocatalytic Mechanism and Structure-Activity Relationship -- Mechanism of Photocatalysis -- In-situ Characterization of Photocatalytic Activity -- Part II Design, Preparation and Modification of Photocatalysts -- Titanium-based Mesoporous Materials for Photocatalysis -- Preparation of Reduced TiO2-x for Photocatalysis -- Graphene Modified TiO2 with Enhanced Visible Light Photocatalytic Activity -- Phase Control of TiO2 Photocatalyst -- Construction of g-C3N4/TiO2 Heterojunction Photocatalyst -- Modifications of Photocatalysts by Doping Methods -- Porous and Cavity-type Photocatalyst -- Part III Photocatalysts for Environmental and Energy Applications -- Heterogeneous Photo-Fenton Technology -- Visible-light Driven Photocatalysts for Selective Redox Reactions -- Cocatalysts for Efficient CO2 Photoreduction -- Part IV Non-TiO2 Photocatalysts -- Syntheses and Applications of Silver Halide-based Photocatalysts -- Synthesis and Modifications of Mesoporous g-C3N4 Photocatalyst -- MoS2 Applications in Photo-Fenton Reaction -- Preparation and Application of CoP Photocatalyst -- Novel Porous Metal Organic Frameworks (MOFs) for water splitting. .
Keywords: Catalysis; Renewable energy sources; Nanotechnology; Refuse and refuse disposal; Materials -- Analysis; Catalysis; Renewable Energy; Nanotechnology; Waste Management/Waste Technology; Characterization and Analytical Technique